2012
DOI: 10.4103/2229-3485.100666
|View full text |Cite
|
Sign up to set email alerts
|

Management of third stage of labor with misoprostol: A comparison of three routes of administration

Abstract: Background and Context:Misoprostol is a versatile drug with an effective uterotonic effect on the postpartum uterine tissue and is used through various routes during the third stage of labor.Aims and Objectives:A randomized prospective study was carried out to analyze the most effective route for misoprostol administration, with an emphasis on parturients’ acceptability and compliance, a possible shortening of the duration of the third stage of labor, minimization of blood loss and possibly reducing the incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…The incidence in oral group is 32%, this is correlating with Bajwa et al =36%. 15 In sublingual group it is 30%, correlating well with Hoj et al-31%. 13 In rectal group, side effects are minimum of 14%, correlating with Bajwa et al-12%.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…The incidence in oral group is 32%, this is correlating with Bajwa et al =36%. 15 In sublingual group it is 30%, correlating well with Hoj et al-31%. 13 In rectal group, side effects are minimum of 14%, correlating with Bajwa et al-12%.…”
supporting
confidence: 74%
“…13 The mean blood loss in present study was 353 ml, it was minimal in sublingual group (305 ml) which is correlating with Bajwa et al 210 ml, Hoj et al, 443ml. 13,15 In oral route it was 356ml which is correlating with Bajwa et al 206ml, in rectal route 398 ml which is correlating with Bajwa 15 et al 236 ml and Neeta et al 230ml. 12,15 The blood loss in sublingual route is significantly less than other routes.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Several other studies 8,20 have also observed that peripartum fall in hematocrit level by at least 10% from before delivery to 24 hours after delivery, is a better definition than the volume criteria of PPH. In this study the efficacy of the two regimes in the active management of the third stage of labour was mainly based on assessment of the degree of fall in hematocrit following delivery in the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Several other studies, Bugalho et al and Bajwah et al have also shwon that peripartum decrease in haematocrit level by at least 10% from pre-delivery to 24 hours postdelivery, is a better definition than the volume criteria of PPH. 17,18 In these studies, the effectiveness of the two regimes in the active management of the third stage of labour was primarily based on measurement of the degree of fall in haematocrit following delivery in the two study groups.…”
Section: Discussionmentioning
confidence: 99%